Language and culture in health communication in an emergency context: do health practitioners and patients talk differently about uncertainty and risk? - Nissen, Vanda; Meuter, Renata F. I. (Frontiers in Communication, 2023)
Objective To explore how expressions of uncertainty are used and understood by patients and their health practitioners (HPs) in language-concordant vs. language-discordant consultations and to invoke CAT to identify the use of communication strategies, with a focus on HPs. Methods This qualitative study encompassed 15 transcribed video and audio recordings of medical consultations between monolingual and bilingual patients and HPs captured in an Australian Emergency Department (ED). HPs and patients also completed a Language Background Questionnaire (LBQ). The main outcome measures included the number and type of expressions of risk and uncertainty used by patients and HPs and the strategies used by HPs to accommodate their patients' conversational needs. Results A total of 15 representative conversations were analyzed, involving two bilingual and two monolingual HPs and 14 patients (of whom five were bilingual). All conversations contained epistemic expressions (e.g., probably), which were used more frequently by patients and more often by bilingual patients. HPs accommodated the patients effectively overall, but some bilingual patients showed difficulties in their understanding. Conclusion All interlocutors expressed uncertainty to varying degrees. The greater use of uncertainty expressions by (bilingual) patients suggests that HPs could increase their communicative effectiveness by attending specifically to their patients' uncertainty talk. Such talk may reflect a need for reassurance. For culturally and linguistically diverse patients, it may reflect issues with comprehension.